Structure, MESP and HOMO-LUMO study of 10-Acetyl- 10H-phenothiazine 5-oxide using vibrational spectroscopy and quantum chemical methods - Bhawani Datt Joshi; Poonam Tandon; Sudha Jain (Bibechana, 2012)
In this communication, we have presented the geometry optimization, complete vibrational study with potential energy distribution (PED) and frontier orbital energy gap for the 10-Acetyl-10H-phenothiazine 5-oxide (APTZ) molecule using ab initio Hartree-Fock (HF) and density functional theory (DFT/B3LYP) method employing 6-311++G(d,p) basis set. The calculated IR and Raman spectra with their intensities, molecular electrostatic potential (MESP) surface and highest occupied molecular orbital (HOMO) - lowest unoccupied molecular orbital (LUMO) plot have been given.